Peran Tata Usaha Bagian Umum Dalam Meningkatkan Pelayanan Sosial Di Kantor Bupati Kabupaten Langkat - Salsabila Matondang; Yenni Samri Nasution (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This study intends to ascertain the impact of public servant performance on community services provided by the Langkat Regent's Office. In this study, data were gathered through interviews using a qualitative methodology. The belief that professional human resources are the foundation for the government's success as a defender of society through the transformation of skills from manual systems to Android and digital systems is crucial for policymakers to share in order to improve communication and make it professional. in volunteer work. In this way, the Langkat Regency Government faces significant challenges. However, at this time both the Regional Government and Village Government are working harder to implement the E-Gov model, beginning with giving officials the skills they need to use more specialized apps through technical support or training. The questions are not all fully addressed by this, though. The interview's findings confirmed that the General and Administrative Section at the Langkat Regent's Office had performed well, and that the Regional Government had implemented its responsibilities and functions by delivering high-quality and efficient public services.